Fatty Acid Percentage Distribution in Complex Lipids of Breast Milk From Mothers on a Low Docosahexaenoic Acid Diet - Gonzalez, Horacio Federico (2023)
The aim of this study was to assess the fatty acid (FA) percentage distribution in complex lipids of breast milk from mothers on a low docosahexaenoic acid (DHA) diet. We performed a descriptive, cross-sectional study of milk samples (n = 14) collected 90 days after delivery and analyzed them using gas chromatography, thin-layer chromatography, and the Fiske-Subbarow method. Complex lipid distribution was 40.70 ± 5.11% sphingomyelin (SM), 26.03 ± 5.98% phosphatidylethanolamine (PE), 21.12 ± 2.32% phosphatidylcholine, 7.94 ± 1.96% phosphatidylserine, and 4.22 ± 1.25% phosphatidylinositol. Median DHA and arachidonic acid values were 0.13% (0.12; 0.18) and 0.42% (0.33; 0.53), respectively. Mean FA percentage in SM and PE was as follows: palmitic acid, 34.45 ± 1.94% and 5.38 ± 0.94%; oleic acid, 16.50 ± 4.07% and 9.43 ± 4.05%; linoleic acid, 5.91 ± 4.69% and 9.05 ± 4.5%. DHA was not detectable in SM, but it was found in PE (55.33 ± 14.46). In conclusion, breast milk of mothers on a low DHA diet contained 55% DHA in PE, but no DHA in SM.